Macrophage regulation in vascularization upon regeneration and repair of tissue injury and engineered organ transplantation - Wenya Li; Zilu Xu; Binghan Zou; Dongcheng Yang; Yue Lu; Xiaohan Zhang; Chen Zhang; Yanzhao Li; Chuhong Zhu (Fundamental Research)
Tissue engineering and regenerative medicine are effective strategies for the treatment of damaged tissues and end-stage organ failure. Damaged tissue regeneration and organ transplantation require blood vessel reconstruction to facilitate tissue remodeling, the bottleneck for application research in this field. Immune cells are heavily involved in coordinating neovascularization, in which macrophage aggregation is a key factor in angiogenesis and arteriogenesis. Previous studies have promoted tissue vascularization by regulating macrophages; however, the mechanisms underlying macrophage-mediated vascularization remain nebulous. Studies on material-based regulation have primarily been observational and lack systematic and targeted research. Macrophages from different sources exhibit different phenotypes or functions in tissues, such as peripheral blood monocytes and tissue-resident macrophages, with each exhibiting complicated mechanisms for promoting tissue injury and graft remodeling. Therefore, in this review, we discuss the role of different tissue-resident macrophages and circulating monocytes in vascularization during injured tissue regeneration and graft remodeling and summarize the current strategies for the use of biomaterials to regulate macrophages and promote the vascularization of injured tissues and during organ transplantation. A better understanding of these mechanisms will facilitate future tissue engineering research that promotes vascularization by regulating macrophage reactions.